Changes in fish communities on a small spatial scale, an effect of increased habitat complexity by an offshore wind farm. (May 2017) - van Hal, R.; Griffioen, A.B.; van Keeken, O.A.
Abstract: The number of offshore wind farms (OWF) is increasing to meet the demands for renewable energy. The piles and hard substrate surrounding these piles creates new habitat for species with preference to hard substrates. We studied the impact of this hard substrate on the fish community in a Dutch OWF in the sandy southern North Sea, which had been in operation for five years. Multi-mesh gillnets were placed near the OWF structures on the hard substrate protection revetments and on the sandy bottom in the middle of the farm. The catches indicated attraction of cod, pouting, bullrout and edible and velvet crab, while attraction to the sandy habitat was shown for flatfish and whiting. Further, two species previously not caught in this area, goldsinny wrasse and grey trigger fish, were caught on the hard substrate. In addition a Dual-Frequency Identification Sonar (DIDSON) was used to record transects through the farm to observe individual fish in the water column throughout the farm and very near the OWF structures. High abundances of fish near the structure were observed during some days, while during other days equal distribution of fish in the area was observed. The area around the structures is thus only used temporarily for shelter or feeding. The DIDSON also allowed looking at the aggregation level of the fish. Seasonally the aggregation level differed most likely due to different species occurring in the area. In April, most fish were aggregated in schools, while in summer most observations were individual fish or loose aggregations. The wind farm structures had limited effect on the aggregation level compared to season or weather conditions. Highlights: Multi-mesh gillnet catches near monopile structures showed attraction of this cod, bullrout, edible crab, velvet crab. Avoidance of the hard-substrate surrounding monopiles was shown for flatfish species and whiting. Increased abundance of fish in the vicinity of monopiles was shown only during two of the five days with DIDSON observations. The monopile structure did not clearly affect the schooling behaviour of the fish in the vicinity.